Role of Peroxisome Proliferator-Activated Receptor-γ in Vascular Inflammation - Kousei Ohshima; Masaki Mogi; Masatsugu Horiuchi (International Journal of Vascular Medicine)
Vascular inflammation plays a crucial role in atherosclerosis, and its regulation is important to prevent cerebrovascular and coronary artery disease. The inflammatory process in atherogenesis involves a variety of immune cells including monocytes/macrophages, lymphocytes, dendritic cells, and neutrophils, which all express peroxisome proliferator-activated receptor-γ (PPAR-γ). PPAR-γ is a nuclear receptor and transcription factor in the steroid superfamily and is known to be a key regulator of adipocyte differentiation. Increasing evidence from mainly experimental studies has demonstrated that PPAR-γ activation by endogenous and synthetic ligands is involved in lipid metabolism and anti-inflammatory activity. In addition, recent clinical studies have shown a beneficial effect of thiazolidinediones, synthetic PPAR-γ ligands, on cardiovascular disease beyond glycemic control. These results suggest that PPAR-γ activation is an important regulator in vascular inflammation and is expected to be a therapeutic target in the treatment of atherosclerotic complications. This paper reviews the recent findings of PPAR-γ involvement in vascular inflammation and the therapeutic potential of regulating the immune system in atherosclerosis.